Ground‐ and satellite‐based evidence of the biophysical mechanisms behind the greening Sahel. (8th January 2015) - Brandt, Martin; Mbow, Cheikh; Diouf, Abdoul A.; Verger, Aleixandre; Samimi, Cyrus; Fensholt, Rasmus
Abstract After a dry period with prolonged droughts in the 1970s and 1980s, recent scientific outcome suggests that the decades of abnormally dry conditions in the Sahel have been reversed by positive anomalies in rainfall. Various remote sensing studies observed a positive trend in vegetation greenness over the last decades which is known as the re‐greening of the Sahel. However, little investment has been made in including long‐term ground‐based data collections to evaluate and better understand the biophysical mechanisms behind these findings. Thus, deductions on a possible increment in biomass remain speculative. Our aim is to bridge these gaps and give specifics on the biophysical background factors of the re‐greening Sahel. Therefore, a trend analysis was applied on long time series (1987–2013) of satellite‐based vegetation and rainfall data, as well as on ground‐observations of leaf biomass of woody species, herb biomass, and woody species abundance in different ecosystems located in the Sahel zone of Senegal. We found that the positive trend observed in satellite vegetation time series (+36%) is caused by an increment of in situ measured biomass (+34%), which is highly controlled by precipitation (+40%). Whereas herb biomass shows large inter‐annual fluctuations rather than a clear trend, leaf biomass of woody species has doubled within 27 years (+103%). This increase in woody biomass did not reflect on biodiversity with 11 of 16 woody species declining in abundance over the period. We conclude that the observed greening in the Senegalese Sahel is primarily related to an increasing tree cover that caused satellite‐driven vegetation indices to increase with rainfall reversal.